The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s12160-011-9272-2
|View full text |Cite
|
Sign up to set email alerts
|

The Conjoined Effect of Naturalistic Perceived Available Support and Enacted Support on Cardiovascular Reactivity During a Laboratory Stressor

Abstract: Together, these findings support the assumption that different aspects of social support are related to different physiological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…These studies tend to provide evidence for the stress-buffering hypothesis by reporting reduced cardiovascular reactivity when a supportive "other" is present (see Uchino et al [2011] for a discussion of factors that can moderate this association). Consistent with the stress-buffering hypothesis, Lee et al (2012) found that psychometrically assessed social support was associated with reduced heart rate (HR) reactivity, while Schwerdtfeger and Schlagert (2011) reported lower HR reactivity in those with high perceived social support during an enacted support condition in a sample of young adults. Additionally, Clark (2003) reported that high perceived social support was associated with lower blood pressure reactivity.…”
Section: Introductionmentioning
confidence: 83%
“…These studies tend to provide evidence for the stress-buffering hypothesis by reporting reduced cardiovascular reactivity when a supportive "other" is present (see Uchino et al [2011] for a discussion of factors that can moderate this association). Consistent with the stress-buffering hypothesis, Lee et al (2012) found that psychometrically assessed social support was associated with reduced heart rate (HR) reactivity, while Schwerdtfeger and Schlagert (2011) reported lower HR reactivity in those with high perceived social support during an enacted support condition in a sample of young adults. Additionally, Clark (2003) reported that high perceived social support was associated with lower blood pressure reactivity.…”
Section: Introductionmentioning
confidence: 83%
“…We found that racial discrimination was associated with HF‐HRV under stress, even after controlling for baseline HF‐HRV. Some previous data show that chronic psychological vulnerabilities such as low social support (Schwerdtfeger & Schlagert, ) may exert their effect, or exert a stronger effect, under conditions of acute stress. These findings may have clinical significance since it has been demonstrated that HRV responses to laboratory challenge correlate well with HRV response to naturalistic stressors (Dikecligil & Mujica‐Parodi, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature documents a supporting role of the vagus in emotional regulation and pro-social behavior. Adults with high vagal tone show greater self-regulatory capacity [138], better regulation of negative facial expressions [139, 140], increased perceived social support [141], and increased feelings of social integration and acceptance [142]. Vagal tone has also been shown to moderate the impact of negative life experiences, acting as a buffer to shield at risk individuals from negative emotional and physical consequences [143145].…”
Section: Discussionmentioning
confidence: 99%